2022
DOI: 10.3390/ijms23020759
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Promotes Antler Growth by Accelerating MT1-Mediated Mesenchymal Cell Differentiation and Inhibiting VEGF-Induced Degeneration of Chondrocytes

Abstract: The sika deer is one type of seasonal breeding animal, and the growth of its antler is affected by light signals. Melatonin (MLT) is a neuroendocrine hormone synthesized by the pineal gland and plays an important role in controlling the circadian rhythm. Although the MLT/MT1 (melatonin 1A receptor) signal has been identified during antler development, its physiological function remains almost unknown. The role of MLT on antler growth in vivo and in vitro is discussed in this paper. In vivo, MLT implantation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Meanwhile, Suttie found a strong positive correlation between antler growth rate and circulating IGF-1 concentration, which interacts with testosterone to stimulate intense antler growth 8 . Moreover, previous studies revealed a series of growth factors and signaling pathways involved in the regulation of antler regrowth, including IGF-1 , parathyroid hormone-related peptide, retinoid acid, melatonin, and Wnt signaling pathway 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Suttie found a strong positive correlation between antler growth rate and circulating IGF-1 concentration, which interacts with testosterone to stimulate intense antler growth 8 . Moreover, previous studies revealed a series of growth factors and signaling pathways involved in the regulation of antler regrowth, including IGF-1 , parathyroid hormone-related peptide, retinoid acid, melatonin, and Wnt signaling pathway 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have demonstrated that melatonin induces a recovery in the functionality of adult hippocampal neurogenesis in aged and neurodegenerative brains of mice with accelerated senescence [ 13 ]. In this respect, Sun and collaborators (2022) also showed that melatonin promotes antler growth in sika deer by accelerating MT1-mediated mesenchymal cell differentiation and inhibiting VEGF-induced degeneration of chondrocytes [ 20 ]. Given the impact of melatonin on cell differentiation processes, an important door is opened towards its potential on cell regeneration mechanisms that should be further investigated.…”
mentioning
confidence: 99%